(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study evaluated the usability of the e-SUS Território system from the perspective of community health agents in a municipality in Alagoas. A mixed-method approach was adopted, using the System Usability Scale (SUS) to collect data from 12 Family Health Strategy teams. Results indicated an 82% approval rating, demonstrating the system’s effectiveness in supporting daily professional tasks. However, technological proficiency was identified as a challenge. The findings highlight the importance of continuous improvement and attentive listening to users as essential strategies to strengthen digital health and promote more efficient and humanized care in primary health settings.